(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article explores dialogical methodology as an effective psychological mechanism for preventing and resolving conflicts between students and teachers in the educational environment. The study analyzes the theoretical foundations of dialogical interaction and its role in establishing constructive communication in the pedagogical process. Particular attention is given to the importance of open dialogue, mutual respect, empathy, and active listening as key factors in reducing misunderstandings and tensions between participants of the educational process. The article emphasizes that dialogical methodology contributes to the development of students’ self-expression, reflective thinking, and cooperative problem-solving skills. The implementation of dialogical approaches in teaching practice is shown to strengthen trustful relationships between teachers and students and to create a positive psychological climate in the classroom. As a result, dialogical methodology serves as an important pedagogical and psychological tool for effective conflict prevention and resolution in educational institutions.